2021
DOI: 10.1155/2021/4389967
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antimicrobial Activity of Subcritical CO2 Extract of Lepidium latifolium L. (Brassicaceae)

Abstract: The genus Lepidium L. from Brassicaceae Burnett. family covers over 150 species with an almost cosmopolitan spread. In Kazakhstan, 21 species are described, of which four species are characterized by medicinal properties (L. crassifolium Waldst. et Kit., L. perfoliatum L., L. ruderale L., and L. latifolium L.), used in folk medicine as means of antibacterial, irritant, laxative, antitumor, analgesic, and anthelmintic action. Methods. Raw materials were collected from Almaty region (Republic of Kazakhstan). Lep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…indica bark extract is another part of the plant that possesses antibacterial potential [104] . Some studies have shown that the bark extracts contain compounds such as quercetin and beta-sitosterol, which exhibit antibacterial activity against various pathogenic bacteria [107,108] . It is important to note that while A. indica extracts have shown promising antibacterial properties in vitro, further research is required to explore their efficacy in vivo and their potential use in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…indica bark extract is another part of the plant that possesses antibacterial potential [104] . Some studies have shown that the bark extracts contain compounds such as quercetin and beta-sitosterol, which exhibit antibacterial activity against various pathogenic bacteria [107,108] . It is important to note that while A. indica extracts have shown promising antibacterial properties in vitro, further research is required to explore their efficacy in vivo and their potential use in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers monitored the participants' hemoglobin levels before and after the six‐month supplement period. The results showed a significant increase in mean hemoglobin levels from 8.23 ± 0.49 to 11.11 ± 0.46 after the follow‐up period (Azimkhanova et al., 2021 ).…”
Section: Industrial Applicationsmentioning
confidence: 98%
“…Advantages of CO 2 -extraction under subcritical conditions compared to supercritical are primarily due to the fact that this process is highly cost-effective, more technologically advanced, allows processing not only high-quality raw materials, but also production waste in order to extract the main components from them [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%